(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Background: Choledochal cyst is an uncommon congenital condition marked by single or multiple dilatations of the intra and/or extrahepatic biliary tree. The cause of choledochal cyst is still unknown, despite numerous theories being offered. Choledochal cysts are often classified into numerous groups based on anatomical findings. In this study, choledochal cysts were treated by total cyst excision and biliary-enteric repair via hepaticojejunostomy (HJ) with or without Roux-en-Y. Aim & Objective: To evaluate the outcomes of hepaticojejunostomy with and without Roux-en Y. Methods: It was a Quasi Experimental Study conducted at the Department of Pediatric Surgery, Dhaka Medical College Hospital, Dhaka, from March 2019 to September 2020. All Children with type I & IV choledochal cyst admitted in the Department of Pediatric Surgery, DMCH, were considered as the study population. Total 40 patients were divided into two groups by computer-generated simple random sampling selection. Group A (Study group): Hepaticojejunostomy without Roux-en-Y, Group B (Control group): Hepaticojejunostomy with Roux-en-Y. Statistical analysis was carried out using the Statistical Package for Social Sciences version 23.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Results: Females made up the majority in both groups 15 (75%) and 16(80%) respectively. One patient (5%) had anastomotic leakage in Group A and two patients (10%) had anastomotic leakage in Group B. The mean time to establish oral feeding in day was 3.70 (±0.65) in Group A and was 5.50 (±1.19) in Group B. The mean duration of hospital stay in day was 8.0 (±1.21) in Group A and in group B it was 9.80 (±1.28). Febrile episodes, after operation at 15 days follow up in group A was 3(15%) and was 4(20%) in group B. At 1st month follow up, fever after operation was 01(5.00%) in group A and was 03 (15.00%) in group B. At 3rd month follow up and 6th month follow up, no USG abnormality was found in both groups. At 15 days follow up the mean SGPT is 72.85 (±11.49) in study group A and is 63.45(±9.52) in study group B, that was statistically significant. Other follow ups such as mean serum bilirubin and mean ALP were not significantly different between two groups. Conclusion: In choledochal cyst, complete excision of cyst and good bilioenteric anastomosis should be done. Hepaticojejunostomy without Roux-en-Y is a simple, quick procedure with preservation of normal anatomy and physiology and minimum complications. So, it can be adopted as a better approach. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 8-14